PENGARUH MEDIA SOSIAL INSTAGRAM, KUALITAS PELAYANAN DAN HARGA DISKON TERHADAP KEPUTUSAN PEMBELIAN GRABFOOD DI ERA PANDEMI COVID-19 - Sanjaya, Jeffry Alvian; Lukman, Iing; Indriani, Wiewiek; Wuryanti, Lestari; Muhammad, Muhammad (Jurnal Jejama Manajemen Malahayati, 2023)
Abstrak (Abstract)Grabfood is one of Grab's service features that provides ordering services to the delivery of food or drinks to the consumer's location. Grabfood cooperates with the best restaurants and outlets. Presenting various types of food, both food and beverages in the country and abroad (Western, Asian, European, Fusion and so on). The aim of this research is to determine the effect of Instagram social media, service quality and discounted prices on Grabfood purchasing decisions in the Covid-19 pandemic era.Analysis in this study is both descriptive and quantitative. The population in this study was all Grabfood consumers in Bandar Lampung who were observed for 1 month with an average number of 65 people or 780 people per year, with a total sample of 264 people. Questionnaire-based data collection and multiple regression analysis.The results of the study show that there partial of Instagram social media on the purchase decision of Grabfood. There partial service quality on Grabfood purchasing decisions. There partial discounted prices on Grabfood's purchasing decisions. There simultaneous of Instagram social media, service quality and discounted prices on Grabfood purchasing decisions.Suggestions for Grabfood to build relationships with users through Instagram social media by making media plans for interactive content on IG Feeds and IG Stories to increase engagement. This can make it easier for a brand to convey messages to consumers and increase brand salience. Keywords: Instagram, Service Quality, Discount Price, Purchase Decision, Grabfood.